If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xy(4x + -5y) = 0 (4x * 3xy + -5y * 3xy) = 0 Reorder the terms: (-15xy2 + 12x2y) = 0 (-15xy2 + 12x2y) = 0 Solving -15xy2 + 12x2y = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3xy'. 3xy(-5y + 4x) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'xy' equal to zero and attempt to solve: Simplifying xy = 0 Solving xy = 0 Move all terms containing x to the left, all other terms to the right. Simplifying xy = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-5y + 4x)' equal to zero and attempt to solve: Simplifying -5y + 4x = 0 Reorder the terms: 4x + -5y = 0 Solving 4x + -5y = 0 Move all terms containing x to the left, all other terms to the right. Add '5y' to each side of the equation. 4x + -5y + 5y = 0 + 5y Combine like terms: -5y + 5y = 0 4x + 0 = 0 + 5y 4x = 0 + 5y Remove the zero: 4x = 5y Divide each side by '4'. x = 1.25y Simplifying x = 1.25ySolution
x = {1.25y}
| 5-20=8x-4-7x | | 8a-(a-4)= | | 2h-8=10-4h | | 7y-3=3y+25 | | 42+5=71 | | 2ba+3ab= | | 1/2X1/2=2/5 | | logx(20)=3 | | 3y-11=21 | | 3x+m=16 | | -2.8/7 | | factorisemn=m | | 3(2x-1)=x+27 | | 15-4(2a-1)= | | 3(x-4)=24 | | 4cosx+1=0 | | y=9x^3-7x+2 | | 4c-1=-5 | | 12t=howmenylb | | X+7.1=4.1 | | 3p^2-6p=1 | | 187=88-y | | 1+(4*4)-2= | | S+4.1=8.1 | | 1*10= | | n^2/3-n/6 | | 52x+3=1 | | (3/4)n | | y^2/2=32 | | 9a-8+6a-4= | | 2(3-8)+7= | | y=-5+4sinx |